The Role of Leadership in Forming Organizational Culture Within the Directorate General of Teachers and Educational Personnel Ministry of Education, Culture, Research and Technology - Manurung, Natal; Rivai Zainal, Veithzal; Hakim, Azis (Cv. Syntax Corporation Indonesia, 2023)
The aim of this research is to determine and analyze the role of leaders in shaping organizational culture within the Directorate General of Teachers and Education Personnel of the Ministry of Education, Culture, Research and Technology and to look at supporting and inhibiting factors as well as strategies for improving organizational culture within the Directorate General of Teachers. and Education Personnel from the Ministry of Education, Culture, Research and Technology. This research was conducted using a descriptive qualitative approach method. Primary data sources (data that can be obtained from interviews) and secondary (data obtained and reading sources). The results of the research are that the role of leaders in forming an organizational culture which is measured through being innovative, results-oriented, oriented to all employee interests and detail-oriented in tasks is running according to the rules set in the organization and each employee carries out individual performance indicators as the output of their routine work. Supporting factors include a disciplined attitude that each employee has, understanding the action program and vision and mission of the organization, good communication between leaders and work partners in achieving results, building motivation of leaders and subordinates, administrative processes as performance assessments for each employee. However, the inhibiting factors are that there is no awareness regarding work discipline, there is no employee commitment in carrying out their duties and functions, not all employees fully understand the vision and mission of the organization, there are still high school education so that a work system has not been developed systematically and there is a lack of employee motivation. in increasing competence. The strategy used to improve organizational culture is to create a uniform understanding of the organization's vision and mission using activities such as training or workshops, building training to improve employee competency, building a measurable and transparent reward and punishment system and evaluating the results of employee performance and output. which is done.